2010
DOI: 10.1017/s1751731110000546
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial ecosystem and methanogenesis in ruminants

Abstract: Ruminant production is under increased public scrutiny in terms of the importance of cattle and other ruminants as major producers of the greenhouse gas methane. Methanogenesis is performed by methanogenic archaea, a specialised group of microbes present in several anaerobic environments including the rumen. In the rumen, methanogens utilise predominantly H 2 and CO 2 as substrates to produce methane, filling an important functional niche in the ecosystem. However, in addition to methanogens, other microbes al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
438
2
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 537 publications
(480 citation statements)
references
References 103 publications
23
438
2
17
Order By: Relevance
“…The pH could be responsible for shifts in ruminal microbial diversity, but in the present work pH values were within physiological limits for all of the studied diets. In agreement with our results, many studies have indicated that methane production in the rumen does not depend on the abundance of methanogens, but on their diversity (Morgavi et al, 2010). The mechanism of action of FB-containing diets, which reduce methane production, does not seem to involve propionate as a sink for H 2 , but a different metabolic pathway such as homoacetogenesis, as previously mentioned.…”
Section: Discussionsupporting
confidence: 92%
“…The pH could be responsible for shifts in ruminal microbial diversity, but in the present work pH values were within physiological limits for all of the studied diets. In agreement with our results, many studies have indicated that methane production in the rumen does not depend on the abundance of methanogens, but on their diversity (Morgavi et al, 2010). The mechanism of action of FB-containing diets, which reduce methane production, does not seem to involve propionate as a sink for H 2 , but a different metabolic pathway such as homoacetogenesis, as previously mentioned.…”
Section: Discussionsupporting
confidence: 92%
“…Hydrogen sinks other than CH 4 exist as H 2 can be used in reductive acetogenesis, or for reduction of nitrate or sulphate. Although considered quantitatively unimportant (Morgavi et al, 2010), these alternative H 2 sinks might explain part of the residual variation. Moss et al (2000) assumed that 90% of the H 2 surplus produced during VFA production is recovered in CH 4 .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that DF may cause a transient effect on protozoa. Protozoa serve not only as host for methanogens, but also produce hydrogen in large quantities in a specialized organelle (hydrogenosome; Morgavi et al, 2010). This hydrogen is metabolized by methanogens that are found inside (Finlay et al, 1994) or in close association with protozoal cells (Stumm et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…There are other potential -E-mail: liujx@zju.edu.cn electron acceptors in rumen (Wolin, 1979), such as sulfate, nitrate and fumarate, etc. (Morgavi et al, 2010). Among them fumarate is non-toxic and an intermediate of the pathways of propionate formation (Russell and Wallace, 1997), and has been extensively studied as an alternative electron sink (Castillo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%